Hypoxia-conditioned mesenchymal stem cells (MSC) exosomes attenuate ultraviolet-B (UVB)-mediated malondialdehyde (MDA) and matrix metalloproteinase-1 (MMP)-1 upregulation in collagen loss models - Jessica Angelina; Agung Putra; Setyo Trisnadi; Dedy Hermansyah; Eko Setiawan; Titiek Sumarawati; Nur Dina Amalina (Medicinski glasnik, 2025)
Aim: To investigate the effects of exosome-derived human mesenchymal stem cells (EH-MSCs) on matrix metalloproteinase-1 (MMP)-1 and malondialdehyde (MDA) levels in ultraviolet-B (UVB)-irradiated Wistar rats. Methods: The study used a post-test-only control group design with randomized allocation. Thirty rats were exposed to UVB radiation (302 nm, 150 mJ/cm²) for 8 minutes, five times a week over two weeks. Five groups were established: a healthy control (G1), a negative control (G2), a positive control that received a 200 ?L subcutaneous injection of hyaluronic acid (HA) (G3), a treatment group 1 that received a 200 ?L subcutaneous injection of exosome-derived EH-MSCs (G4), and a treatment group 2 that received a 300 ?L subcutaneous injection of EH-MSCs (G5). An ELISA was used to quantify the levels of MDA and MMP-1. Results: A significant reduction in the mean level of MDA in groups G4 (368.33 ± 59.67) and G5 (329.33 ± 82.06) was noted when compared to the negative control group G2 (686.58 ± 119.01) (p<0.05). Similarly, MMP-1 showed a significant decrease in mean levels for G4 (0.08 ± 0.04) and G5 (0.07 ± 0.04) compared to G2 (0.33 ± 0.06) (p<0.05). Conclusion: These findings suggest that EH-MSCs have potent antioxidant and anti-inflammatory properties, mitigating UVB-induced skin damage by reducing oxidative stress markers.
Keywords: extracellular matrix; hypoxiainduced factors; oxidative stress; photoaging; stem cell therapy